PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN SIKAP DAN PERILAKU PEDULI LINGKUNGAN PESERTA DIDIK MELALUI PEMBELAJARAN IPS - Resti Fauzi Hidayat, - (2021)
This research is motivated by the low attitudes and environmental care behavior of students. This is due to the lack of understanding, knowledge, and analytical skills of students on environmental conditions. This study aims to determine and analyze the improvement of students' environmental care attitudes and behavior by using problem-based learning models in social studies learning at Riyadlul Ulum Wadda'wah Putri Integrated Junior High School. The research method used is quantitative in the form of a quasi-experimental research design with a non-equivalent control group design. The data analysis technique used independent samples t-test. Based on the results of research on social studies learning using a problem-based learning model, it shows that there are differences in the increase in attitudes and environmental care behaviors of students. Where the increase in attitudes and environmental care behavior in the experimental class is better than the control class. This means that the use of problem-based learning models affects improving attitudes and behaviors that care for the environment. Supporting factors that help in improving students' environmental care attitudes and behavior, namely the support from the teacher and the desire of students to learn to understand and analyze environmental problems around them so that they can reflect on every action they will or are taking on the environment for daily life their day. Meanwhile, the inhibiting factors are the facilities and infrastructure and the limited time for research due to the pandemic that has occurred, requiring learning activities to stop.